Corporate Governance and Financial Performance: Exploring the Relationship Between Board Structure, Executive Compensation, and Firm Value - Rokhimah, Zulaika Putri (Accounting Studies and Tax Journal (COUNT), 2024)
This research explores the relationship between board structure, performance-based compensation, and firm value with a focus on the differences between companies with diversified and centralized board structures. Corporate governance plays an important role in determining a company's financial performance, where the board structure functions as the main supervisor. The systematic literature review method with the PRISMA approach was used to analyze and synthesize relevant literature. The research results show that companies with a diversified board structure, covering various aspects such as gender, age and ethnicity, tend to have higher company value compared to companies with a centralized board structure. Diversifying board structures increases the transparency and effectiveness of performance-based compensation, ultimately contributing to better financial performance. These findings offer new insights into how corporate governance can be optimized to increase company value.